WOMEN'S ASPIRATIONS IN Q.S. AL-MUJADILAH [58] VERSE 1: MOHAMMED ARKOUN'S CRITICAL LINGUISTIC REVIEW - Fitri Andriyani (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2022)
Analysis regarding al-Mujādilah verse 1 often only focuses on the incident that happened to Khawlah bint Tsa'labah. In contrast, on the other hand, this verse also talks about the procedures for women in expressing their aspirations. This article wants to elaborate on this side that is rarely highlighted. This is done by conducting a linguistic analysis of QS. al-Mujādilah verse 1. By using critical linguistic theory as the reading framework offered by Arkoun. This paper also attempts to reveal the performative side of the text by examining the critical relationships in verses and the meanings that arise from them. Using critical linguistic theory, it can be found that Arkoun's critical linguistic approach can offer interpretation by understanding the acts that work in the text so that the text's whole meaning can be understood. From critical linguistic analysis, we can move to the level of performative reading, where this verse offers at least two applicative steps for anyone who wants to voice their aspirations, first; carry out protests, discussions, or even debates carried out dialectically, and the second; is to encourage each of these efforts with spiritual practices.